John J. Gilligan : The Politics of Principle - Bernstein, Mark, 1950 January 30- (Book collections on Project MUSE., 2013)
This first full-length biography of John Joyce Gilligan argues that Ohio's sixty-second governor was the most significant Democrat in the state's postwar years. But it is more than the story of a governor. Through painstaking research and dozens of interviews, author Mark Bernstein paints a vivid picture of Ohio's past and its prospects for the future that includes an array of lesser politicians-- some of them outlandish--who aided or opposed Gilligan's efforts. Gilligan did not intend to have a political career. The Cincinnati native resolved to join a Jesuit seminary, but when Pearl Harbor was bombed, he enlisted in the Navy and won the Silver Star at Okinawa. While on leave, Gilligan married the former Katie Dixon, whom he had known since childhood. After the war, the Gilligans settled in Cincinnati where Jack attended graduate school and taught at Xavier University. What drew him into politics was Adlai Stevenson's 1952 presidential campaign, which ignited in Gilligan a belief in politics as public service. His service included a decade on Cincinnati's city council and his 1964 election to Lyndon Johnson's "Great Society" congress as the representative for Ohio's First District. Through these years, Ohio's Democratic Party was largely conservative. It was dominated by five-time governor and two-term senator Frank Lausche. Gilligan allied himself with labor, minorities, and academics to launch the long shot senatorial campaign that defeated the incumbent in the 1968 Democratic primary. Though Gilligan lost by a narrow margin that November, he emerged as the state's leading Democrat and its successful 1970 gubernatorial candidate. By the 1970s, Ohio's ills were manifest. Schools closed for lack of funds; the heavily polluted Cuyahoga River caught fire. Once in office, Gilligan financed improvements by maneuvering the state's first income taxes through a Republican-controlled legislature. He expanded support for education and mental health, while establishing the Ohio EPA and campaign finance reform. It was a record that prompted talk of a Gilligan presidential run in 1976. Bernstein examines the reasons for Gilligan's wholly unexpected defeat for reelection in 1974 and shows that afterward, Gilligan steadfastly pursued his commitment to civic engagement by heading the Peace Studies program at the University of Notre Dame, establishing the Civic Forum at the University of Cincinnati and, in 1999, running successfully for Cincinnati school board--at age 78. John J. Gilligan: The Politics of Principle presents a lively and fascinating portrait of a distinctive figure of postwar American liberalism.